Pengembangan LKPD Fiqh Berbasis Komik Edukasi Model Distance Learning QR Code di SMP Islam al-Amin Nusantara Lampung - Yusuf, Muhammad; Sari, Defika Adriana; Setiawan, Dedi (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2022)
In the process of learning fiqih material in Arabic writing, such as using the Mabadi fiqh book, it is still difficult for some students who basically do not understand the writing, and are then required to understand the content of the material. Without a translation from the teacher, students have not been able to learn independently. Thus, this study aims to develop Fiqih students’ worksheets, and educational comic QR codes, so that students can learn the material easily. The Research and Development (R&D) model used is ADDIE, which includes Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques are based on questionnaires, observations, interviews, and documentation. While the data analysis used a scale of 1-5. Deserve of 5, worthy of 4, worthwhile of 3, unsuitable of 2, and impolitic of 1. Based on the data analysis, the researcher got the final results from the validation of media experts with an average of 79, material experts with an average of 55, linguists with an average of 44, and fiqih teachers with an average of 127. While the results of the trial on 16 students got an average of 65.8. The overall results show that the Fiqih students’ worksheet and educational comic QR code using the ADDIE model deserves, both in terms of media, material and language to be used as teaching, especially in fiqih material.